Private Employers Don't Need Formal Risk Adjustment - Jacob Glazer; Thomas G. McGuire (SAGE Publishing, 2001)
This paper lays down a set of hypotheses to explain why private employers do not use formal risk adjustment. The theme running through these hypotheses is simple: private employers don't need formal adjustment because they have better tools for dealing with adverse selection than formal risk adjustment provides. Open enrollment provisions, premium negotiations, and restricting employees' choices of health plans are mechanisms superior to formal risk adjustment for dealing with problems caused by adverse selection.